Experimental Study on the Role of Apelin-13 in Alleviating Spinal Cord Ischemia Reperfusion Injury Through Suppressing Autophagy - Xu Z; Li Z (Dove Medical Press, 2020)
Zhewei Xu, Zhiyue Li Department of Orthopedics, Third Xiangya Hospital of Central South University, Changsha, Hunan 410013, People’s Republic of ChinaCorrespondence: Zhiyue LiDepartment of Orthopedics, Third Xiangya Hospital of Central South University, Changsha, Hunan 410013, People’s Republic of ChinaTel +861378731 8116Email oirieqnoh@sina.comBackground: This study aimed to explore the effect of Apelin-13 in protecting rats against spinal cord ischemia reperfusion injury (SCIR), as well as the related molecular mechanisms.Methods: One week prior to the experiment, experimental Sprague–Dawley rats were injected with Apelin-13 and the autophagy activator rapamycin through the tail vein once a day for 7 consecutive days. The SCIR rat model was prepared through the abdominal aorta clamping method. At 72 h after injury, the spinal cord tissue water content, infarct volume, and normal neuron count were determined to evaluate the degree of spinal cord tissue injury in the rats. The Basso–Beattie–Bresnahan scoring standard was adopted for functional scoring of the rat hind leg, to reflect the post-injury motor function. At 72 h after injury, changes in mitochondrial membrane potential, reactive oxygen species content, and mitochondrial ATP were detected. ELISA was carried out to detect the malonaldehyde content, as well as catalase, superoxide dismutase, and glutathione catalase activities in spinal cord tissues at 72 h after injury. Quantitative chemistry was conducted to examine the contents of nitric oxide (NO) and endothelial nitric oxide synthase (eNOS) in spinal cord tissues. Finally, the expression of autophagy-related proteins, Beclin1, ATG5, and LC3, in spinal cord tissues was detected through the Western blotting assay.Results: Apelin-13 pretreatment alleviated SCIR, promoted motor function recovery, suppressed mitochondrial dysfunction, resisted oxidative stress, and inhibited autophagy in spinal cord tissues following ischemia reperfusion injury.Conclusion: Apelin-3 exerts protection against SCIR by suppressing autophagy.Keywords: Apelin-13, spinal cord ischemia reperfusion injury, autophagy, rapamycin, oxidative stress, mitochondrion